Theoretical investigations on charge transport properties of tetrabenzo[a, d, j, m]coronene derivatives using different density functional theory functionals (B3LYP, M06-2X, and wB97XD). Issue 7 (July 2019) - Chen, Ziran; Li, Yuan; He, Zhanrong; Xu, Youhui; Yu, Wenhao
Charge transport rate is one of the key parameters determining the performance of organic electronic devices. Based on density functional theory, exchange-correlation functionals which adequately account for non-covalent interactions, such as M06-2X and wB97XD, should significantly improve the accuracy of charge transport rate calculations for large systems with non-covalent interactions. In this work, the B3LYP hybrid functional, the variant hybrid functional M06-2X, and the long-range-corrected wB97XD functional were used to perform geometry optimizations and charge transport rate calculations on 11 variants of tetrabenzo[ a, d, j, m ]coronene, including tetrabenzo[ a, d, j, m ]coronene itself and its tetra-substituted and octa-substituted derivatives. Our results indicate that the molecular geometries of these benzocoronene semiconductors are large quasi-planar conjugated π systems, and the incorporation of different substituents significantly affects their frontier molecular orbitals. The hole carrier mobility ( µ + ) and electron carrier mobility ( µ − ) of the methoxy-substituted derivatives (TBC(OCH3 )4 andTBC(OCH3 )8 ) were relatively low. The results of the tetrabenzo[ a, d, j, m ]coronene molecules studied were consistent with using the aforementioned M06-2X, wB97XD, and B3LYP methods. We found that the octa-substituted derivatives (TBCF8, TBCCl8, TBC(CH3 )8, andTBC(CN)8 ) could be used as p-type organic semiconductor materials.